An estimate of the area of occupancy and population size of Brachycephalus tridactylus (Anura: Brachycephalidae) to reassess its conservation status, with a proposal for conservation measures - Bornschein, Marcos R. [UNESP]; Nadaline, Júnior; Ribeiro, Luiz Fernando; Sandretti-Silva, Giovanna [UNESP]; Rivas, Maria Fernanda Ferreira [UNESP]; De Morais Guerra, Bruno [UNESP]; Teixeira, Larissa [UNESP] (PeerJ, 2021)
Background. We are experiencing a global crisis in conservation, which has led to the prioritization of targets, such as nations, regions, and animal groups, which are necessary while resources are disputed. Brazil is a priority not only because of its megadiversity, high rates of endemism, and frequent descriptions of new species but also because of its high levels of deforestation. Among the species groups prioritized for conservation is the anurans (Amphibia: Anura), the population of which is severely declining. One group of anurans is the genus Brachycephalus, which includes 37 endemic species in the Brazilian Atlantic Rainforest. Some of these species have highly restricted distributions (<100 ha). Thirty new species have been described since 2000, and 55.3% of all species are threatened with extinction. Brachycephalus tridactylus was only recently described and remains restricted to its type locality. Because of its reduced geographical distribution (0.41 km2), it has been proposed to be considered as Vulnerable. The objective of this study is to reevaluate the conservation status of Brachycephalus tridactylus and propose conservation measures. Methods. We searched for new populations during 2016-2020, evaluated in loco impacts and potential impacts on the species' population, and performed an analysis of the density of this population and estimated its size. International Union for Conservation of Nature (IUCN) criteria were used to assess the conservation status of the species. Results. We recorded the species in seven new localities (from 715-1,140 m above sea level) in the state of São Paulo up to 33 km from the type locality of the species (in state of Paraná). We estimated the area of occupancy as 148.44 km2, densities as one calling male per 4.05 m2 and 130.00 m2, and a total population size of 4,429,722 adult individuals. Based on our finding, we proposed three lines of management: (1) formation of fire brigades, (2) management of residents' mules in the conservation unit and surrounding areas, and (3) management of degraded areas. We recommend changing the species' conservation status from Vulnerable to Endangered because of its fragmented distribution and decline in the area of occupancy and in the quality of its habitat. Our results have expanded the species previous geographic distribution and delimited areas without previous records. Our estimates of population density and size are in accordance with those verified for congeners. The conservation of this species benefits the environments and other species that inhabit them, being, therefore, strategic for receiving conservation actions that will spread throughout the ecosystem.
Keywords: Bamboo impacts; Density; Edge effect; Endangered; Forest fire; Fountain species; Geographic distribution; Management; Palm heart harvesting; Secondary vegetation